Optimal Sequential Decision Architectures and the Robustness of Hierarchies and Polyarchies - KOH, Winston T. H. (Institutional Knowledge at Singapore Management University, 2005)
This paper studies collective decision making in the context of a project selection model. We derive the optimal decision architecture in the presence of marginal decision costs, and investigate the circumstances under which the hierarchy and polyarchy emerge as optimal sequential architectures. Our analysis extends previous results on optimal organizational decision-making to a sequential setting, and further demonstrates the fragility of the hierarchy and polyarchy as optimal architectures.